2007
DOI: 10.1158/1535-7163.mct-06-0609
|View full text |Cite
|
Sign up to set email alerts
|

Detailed DNA methylation profiles of the E-cadherin promoter in the NCI-60 cancer cells

Abstract: E-cadherin (E-cad) is a transmembrane adhesion glycoprotein, the expression of which is often reduced in invasive or metastatic tumors. To assess E-cad's distribution among different types of cancer cells, we used bisulfitesequencing for detailed, base-by-base measurement of CpG methylation in E-cad's promoter region in the NCI-60 cell lines. The mean methylation levels of the cell lines were distributed bimodally, with values pushed toward either the high or low end of the methylation scale. The 38 epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
39
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 53 publications
(52 reference statements)
10
39
1
Order By: Relevance
“…While some E-cadherin promoter methylation data has shown much higher percentages of DNA methylation, our data are consistent with previous findings showing that a threshold of 20-30% is sufficient for E-cadherin gene silencing. 34 This supports evidence that, while histone modifications may prime a gene for silencing and cause low expression, the addition of DNA methylation is necessary to induce complete silencing. 38,39,52 Therefore, a gradient of epigenetic gene silencing may exist during the progression of cancer that dictates which genes are irreversibly silenced and which remain in a transient linked to their cellular microenvironment, as methylation-mediated gene silencing of the E-cadherin promoter is dynamically influenced by induction of complex cell-cell and cell-matrix interactions in the context of a 3D tissue.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…While some E-cadherin promoter methylation data has shown much higher percentages of DNA methylation, our data are consistent with previous findings showing that a threshold of 20-30% is sufficient for E-cadherin gene silencing. 34 This supports evidence that, while histone modifications may prime a gene for silencing and cause low expression, the addition of DNA methylation is necessary to induce complete silencing. 38,39,52 Therefore, a gradient of epigenetic gene silencing may exist during the progression of cancer that dictates which genes are irreversibly silenced and which remain in a transient linked to their cellular microenvironment, as methylation-mediated gene silencing of the E-cadherin promoter is dynamically influenced by induction of complex cell-cell and cell-matrix interactions in the context of a 3D tissue.…”
Section: Discussionsupporting
confidence: 71%
“…Previous data examining CpG methylation within the E-cadherin promoter has shown that above a threshold of 20-30% methylation, E-cadherin gene expression is silenced. 34 Significantly, this same study showed consistent methylation at one specific CpG, which stromal compartment maintained loss of E-cadherin expression (Fig. 4B, thick arrow).…”
Section: Resultssupporting
confidence: 57%
“…This is critical for biological analysis, since epigenetic information is often chromosome-specific, e.g., imprinted genes. Furthermore, DNA methylation may have a threshold effect for regulating gene expression, e.g., ∼25% for E-cadherin in a broad range of cell types (Reinhold et al 2007). Note that transforming M directly into estimates of absolute methylation is not straightforward.…”
Section: Quantification Of Methylation Measurementsmentioning
confidence: 99%
“…In the HT29 and HCT116 models many integrins and tetraspanins, such as ß1-integrin, CD9 or CD81, were up-regulated, whereas these genes were down-regulated in Co5841, Co5776 and LoVo. Besides that, E-cadherin, an important suppressor of epithelial tumor cell invasiveness and metastasis which is epigenetically silenced through promoter methylation in many carcinomas (47), was downregulated in the non-responder models Co5841 and Co5776 upon MS-275 treatment. This implies that MS-275 did not induce the re-expression of E-cadherin, but rather promoted the hypermethylated status of the primary non-responder models.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that MS-275 did not induce the re-expression of E-cadherin, but rather promoted the hypermethylated status of the primary non-responder models. E-Cadherin as well as claudin 4 (CLDN4), which were down-regulated in Co5776, are decreased in diffuse type and poorly differentiated tumors (47,48). Dysfunction of these proteins may therefore play a role in disruption of cellcell adhesion.…”
Section: Discussionmentioning
confidence: 99%